Hypoxia, Hypoxia-Inducible Factors and Liver Fibrosis - Beatrice Foglia; Erica Novo; Francesca Protopapa; Marina Maggiora; Claudia Bocca; Stefania Cannito; Maurizio Parola (Cells, 2021)
Liver fibrosis is a potentially reversible pathophysiological event, leading to excess deposition of extracellular matrix (ECM) components and taking place as the net result of liver fibrogenesis, a dynamic and highly integrated process occurring during chronic liver injury of any etiology. Liver fibrogenesis and fibrosis, together with chronic inflammatory response, are primarily involved in the progression of chronic liver diseases (CLD). As is well known, a major role in fibrogenesis and fibrosis is played by activated myofibroblasts (MFs), as well as by macrophages and other hepatic cell populations involved in CLD progression. In the present review, we will focus the attention on the emerging pathogenic role of hypoxia, hypoxia-inducible factors (HIFs) and related mediators in the fibrogenic progression of CLD.